Directed midbrain and spinal cord neurogenesis from pluripotent stem cells to model development and disease in a dish - Allodi, Ilary; Hedlund, Eva (Frontiers in Neuroscience, 2014)
Induction of specific neuronal fates is restricted in time and space in the developing CNS through integration of extrinsic morphogen signals and intrinsic determinants. Morphogens impose regional characteristics on neural progenitors in a concentration-dependent fashion and establish distinct progenitor domains. Such domains are defined by unique expression patterns of fate determining transcription factors. These processes of neuronal fate specification can be recapitulated in vitro using pluripotent stem cells. In this review, we focus on the generation of dopamine neurons and motor neurons, which are induced at ventral positions of the neural tube through Sonic hedgehog (Shh) signaling, and defined at anteroposterior positions by fibroblast growth factor (Fgf) 8, Wnt1, and retinoic acid (RA). In vitro utilization of these morphogenic signals typically results in the generation of multiple neuronal cell types, which are defined at the intersection of these signals. If the purpose of in vitro neurogenesis is to generate one cell type only, further lineage restriction can be accomplished by forced expression of specific transcription factors in a permissive environment. Alternatively, cell-sorting strategies allow for selection of neuronal progenitors or mature neurons. However, modeling development, disease and prospective therapies in a dish could benefit from structured heterogeneity, where desired neurons are appropriately synaptically connected and thus better reflect the three-dimensional structure of that region. By modulating the extrinsic environment to direct sequential generation of neural progenitors within a domain, followed by self-organization and synaptic establishment, a reductionist model of that brain region could be created. Here we review recent advances in neuronal fate induction in vitro, with a focus on the interplay between cell intrinsic and extrinsic factors, and discuss the implications for studying development and disease in a dish.